2018
DOI: 10.1093/ntr/nty252
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Systems-Based Tobacco Cessation Program Using Bedside Volunteers

Abstract: Introduction Hospitalization and post-discharge provide an opportune time for tobacco cessation. This study tested the feasibility, uptake, and cessation outcomes of a hospital-based tobacco cessation program, delivered by volunteers to the bedside with post-discharge referral to Quitline services. Patient characteristics associated with Quitline uptake and cessation were assessed. Methods Between February and November 2016, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Table 3 presents an overview of each study 36‐98 . A summary of the characteristics of the 56 studies is presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 3 presents an overview of each study 36‐98 . A summary of the characteristics of the 56 studies is presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Table 6 presents an overview of the groups, listing the implementation strategy for each group and subsequently providing a breakdown of each implementation outcome (acceptability, adoption, appropr iateness, cost, feasibility, fidelity, penetration, and sustainability). 31,36,37,[39][40][41][42][43][44][45][46][47][48][49][50][51][52]56,58,[60][61][62][64][65][66][67][68][69][70][71]73,75,76,82,[86][87][88][89]91,92,[94][95][96] A more comprehensive list of implementation outcomes for all included studies is presented in Supporting Table 2. A summary of results is presented below:…”
Section: Implementation Outcomes By Implementation Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…Some research has identified barriers to implementing the full 5As model [48,49], and a shorter 3As ‘ask–advise–refer/act/connect’ has been suggested [34,50–52]. These shorter models have been used mainly in ambulatory settings [52] and with a focus on referring patients to telephone Quitline services [53]. The preponderance of knowledge on this topic suggests that delivery of all the components of the 5As model is associated with a greater use of cessation treatments [22].…”
Section: Discussionmentioning
confidence: 99%